2017
DOI: 10.2147/imcrj.s128628
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular eyelashes and iris cyst in anterior chamber following penetrating eye injury: a case report

Abstract: BackgroundThe presence of intraocular eyelashes following penetrating eye injury or ocular surgery is relatively uncommon. The response of the eye to intraocular eyelashes is variable. The eyelash may be symptomatic or may remain asymptomatic for long periods.ObjectiveWe report a case with two intraocular eyelashes and an iris cyst after 2 years of asymptomatic period following penetrating eye injury.Case presentationA 24-year-old male presented with decreased vision in the left eye which he had noticed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Intraocular eyelashes are associated with variable presentations, from asymptomatic to endophthalmitis and retinal detachment. [ 2 3 ] Intraocular cilia have been retained for as little as 6 weeks to beyond 40 years ago. [ 3 4 ] Management approaches vary depending on the clinician and patient presentation, from a watch-and-wait stance to intervention to expel the eyelash.…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular eyelashes are associated with variable presentations, from asymptomatic to endophthalmitis and retinal detachment. [ 2 3 ] Intraocular cilia have been retained for as little as 6 weeks to beyond 40 years ago. [ 3 4 ] Management approaches vary depending on the clinician and patient presentation, from a watch-and-wait stance to intervention to expel the eyelash.…”
Section: Discussionmentioning
confidence: 99%
“…Whether cilia foreign bodies in the posterior segment have to be removed or not through an operation depends on the situation [ 10 ]. Intraocular cilium have been reported to be asymptomatic for 50 year in the anterior chamber [ 11 ]. However, more reports have shown that cilia left in eyes tend to cause polytype endophthalmitis [ 1 , 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The response of the eye to intraocular eyelashes is variable. The eyelash may be symptomatic, intra-ocular cilia can be associated with corneal edema, corneal graft rejection, granulomatous or nongranulomatous iridocyclitis, cyst formation, lens abscess, retinal detachment and endophthalmitis or may remain asymptomatic for long periods [3,4,7,9,10]. The asymptomatic course of intra-ocular cilia is related to its relatively inert nature compared to other organic materials and the immune privileged feature of the eye [3].…”
Section: (A) (B)mentioning
confidence: 99%